Can grafted tubularized incised plate urethroplasty be used to repair narrow urethral plate hypospadias? Its functional evaluation using uroflowmetry - Pradyumna Pan (Wolters Kluwer Medknow Publications, 2019)
Aim: Using uroflowmetry, the aim of this study is to determine the functional results of the grafted tubularized incised plate (GTIP) urethroplasty used to repair poor urethral plate hypospadias. Settings and Design: Seventy-one patients (mean age: 5.7 years, follow-up: 1-5.5 years) were selected from those who underwent surgery using the GTIP technique from 2013 to 2015 at our institution. Methods: Patients included were able to void voluntarily and had no fistula. The flow pattern, maximum urinary flow rate (Qmax), voided volume (vv), average flow rate, and voiding time were measured. The results were expressed as percentiles and interpreted according to Siroky nomogram. The Qmaxwas considered normal if >25th percentile, as equivocally obstructed when in the 5th-25th percentile, and obstructed if <5th percentile. Results: Hypospadias was distal in 45, mid penile in 17 and proximal penile in 9. The uroflow curve was bell-shaped in 24 (30%), interrupted in 9 (14%), slightly flattened in 31 (46%), and a plateau in 7 (10%). Flow rate nomograms revealed that 49 (68%) were above the 25th percentile, 9 (17%) were below the 5th percentile, and 13 (15%) were between these ranges. Eleven patients showed improvement in the flow curve and maximum urinary flow rate (Qmax) in follow-up uroflowmetry. Conclusion: GTIP repair provides satisfactory functional results. A long-term follow-up is needed to confirm these results.